Reception of Islamic Legal Rituals Among Indigenous Indonesian Communities with Comparative Findings from Wetu Telu and Masade - Yusuf, Nasruddin; Willya, Evra; Mash'ud, Imam; Kamma, Hamzah; Imamuddin, Imamuddin (Jurnal Ilmiah Al-Syir'ah, 2025)
This article examines the Reception of Islamic legal rituals among indigenous Indonesian communities through a law-centered comparative design. This study understands reception as the selection, reinterpretation, and substantive integration of Islamic ritual norms into local practice. The framework juxtaposes doctrinal analysis of fiqh (Islamic jurisprudence) categories, namely ibādāt taʿabbudī/tawqīfī (worship rituals strictly bound to canonical pillars and conditions) and muʿāmalāt/ahwāl al-shakhṣiyyah (social transactions and personal status), with ethnographic and historical materials. The analysis assesses four equivalent domains: core obligations of worship, calendrical ordering, sacred space and authority, and life-cycle rites. Findings indicate that the Wetu Telu (Sasak "three times" tradition) community in Lombok exhibits primarily substantive Reception, in which ritual form and legal intent converge and are institutionally embedded. By contrast, the Masade (Sangihe "Old Islam" community) exhibits a more selective and symbolic reception, maintaining Islamic identifiers while limiting ritual obligations and temporal coordination within a localized sacred order. These patterns clarify how ʿurf (customary practice) can sustain or reframe Fiqh in indigenous settings without reducing analysis to a simple binary of "orthodox" versus "syncretic." The article contributes a scalable matrix for assessing ritual reception across communities and highlights implications for legal pluralism and the living law of Islam in Indonesia.